Recovery Rates by Severity of Hearing Loss in Cases of Acute Low-Tone Sensorineural Hearing Loss - So, Hirotaka; Ueno, Masafumi; Sato, Yoichiro; Kasahara, Ken; Fuse, Yoshimitsu; Shinden, Seiichi; Oishi, Naoki; Ozawa, Hiroyuki (International Journal of Practical Otolaryngology, 2025)
Acute low-tone sensorineural hearing loss (ALHL), first reported in 1982, is characterized by hearing loss (HL), tinnitus, and other auditory symptoms. It is a disease entity independent from sudden HL. Although the severity of HL was defined for the first time in 2015 by the Research Group on Intractable Hearing Impairment of the Ministry of Health, Labor and Welfare, only a few studies have examined the treatment outcomes by the severity of HL. In this study, we determined the overall cure rate (cure/all cases) in 336 ALHL cases treated over 11 years (2011–2021) and the cure rates by the severity of the HL and steroid use. The overall cure rate was 64.0%, with 75.0% in cases with grade 1 severity, 74.3% in grade 2, 57.4% in grade 3, and 34.7% in grade 4. The cure rate in grade ¾ cases was significantly lower than that in grade ½ cases. No significant difference was noted in the cure rate by steroid use. The cure rate of sudden HL is dependent on the hearing level at the initial diagnosis, and the cure rate of ALHL can be predicted by the sum of the hearing levels of the three lowest frequencies at the initial diagnosis. Although this study did not demonstrate the efficacy of steroid use, the study design biased the sample population. ALHL is associated with higher recurrence than sudden HL; however, steroids have various side effects. Therefore, the appropriateness of steroid use in the treatment of ALHL should be determined by a thorough assessment of comorbidities, patient age, and disease severity.
Keywords: ALHL; acute sensorineural hearing loss; endolymphatic hydrops